Oxford handbook of women's health nursing - Gupta, Sunanda; Holloway, Debra; Kubba, Ali (Oxford : Oxford University Press, 2021)
This handbook is a concise and handy reference on women's health for nurses and other health professionals working in primary care, community, health promotion or acute settings. It focuses on practical care pathways for common gynaecological conditions.
This edition also issued in print: 2021.
Previous edition: 2010.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 23, 2021).
Keywords: Gynecologic nursing; Women -- Health and hygiene; Women -- Diseases